Project implementation of the hostel upgrade programme in the city of Johannesburg - Fenyane, Tebogo Wiiliam (My University, 2016)
Originally, hostels were developed to accommodate migrant labour in urban areas. With the abolishment of influx control laws in 1986, informal settlements mushroomed close to hostel precincts as relatives and those seeking affordable housing in proximity of employment opportunities flocked to urban areas. Overcrowding, poor maintenance of hostels and the vandalism of the infrastructure resulted in hostels deteriorating and becoming unfit for hygienic human habitation. From the early 1990’s, the government adopted a number of measures (housing programmes) aimed at rehabilitating hostels and converting them into family units. The Hostel Redevelopment Programme as implemented to date has led to upgraded units being built but not allocated to the intended beneficiaries (hostel residents). This failure was partly the result of communication breakdown between hostel communities and local communities. This study attempts to comprehend factors that led to project communication breakdown between the project team and the hostel community. The Johannesburg Housing Company (JOSHCO) is the implementation agent on behalf of the City of Johannesburg tasked with converting single gender hostel compounds into affordable rental units. The report suggested public participation as the suitable process to solve the problem of communication between different actors in the hostel project. The legal framework of public housing emphasises the importance of public participation in the programme of housing provision. The discourse on public participation conceptualises community participation broadly as a strategy aimed at empowering citizens to have a voice in policies decisions that have a bearing on their lives. The legal framework espouses the philosophy of citizen’s involvement in developmental matters having the right to having their views reflected in policy decisions. This study tries to understand the effectiveness of the hostel redevelopment programme public consultation processes in influencing housing option provided to the residents of Diepkloof Hostel and the Orlando West Women’s Hostel. The design of this study is conceptualised using Project Management principles or knowledge areas, focusing specifically on Project Communication. The researcher is of the view that improving the effectiveness of the public participation process, factors that result in the non- occupation of hostels can be avoided. With the massive housing backlog still prevalent in South Africa, consensus is required between all stakeholders (especially hostel residents) on the type of units that are acceptable to the hostel community to provide for successful allocation process, thereby resulting in a successful handing over of housing products that will be sustainable in terms of affordability and give recipients the dignity of adequate shelter.
Research report submitted in accordance with the degree Masters in Management University of the Witwatersrand Public and Development Management , July 2016
Keywords: Johannesburg Housing Company; Migrant labor--Housing--South Africa--Johannesburg